EFEKTIVITAS MODEL PEMBELAJARAN PjBL DENGAN PENDEKATAN DEEP LEARNING MATERI CAHAYA UNTUK MENINGKATKAN BERPIKIR REFLEKTIF SISWA KELAS 5 (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of the Project-Based Learning (PjBL) model with a Deep Learning approach on enhancing the reflective thinking skills of 5th-grade students on the topic of Light. The application of the PjBL model is expected to improve students' understanding of scientific concepts in Science (IPA) learning, as well as develop their reflective thinking skills. The Deep Learning approach used in this research emphasizes deep understanding, not just memorization, to encourage students to think critically and reflectively. The research method used is descriptive quantitative with an experimental design. The study involves two groups of students, namely the experimental group that applies the PjBL model with a Deep Learning approach and the control group that receives conventional learning. Data were collected through pre-tests and post-tests to measure students' reflective thinking abilities, as well as questionnaires to assess students' responses to the implemented learning. The results of the study show that the application of the PjBL model with a Deep Learning approach significantly improves students' reflective thinking abilities, as evidenced by a significant difference between pre-test and post-test results. This research contributes to the development of more active, creative, and reflective Science (IPA) learning and encourages the implementation of project-based learning to enhance the quality of education in elementary schools. Furthermore, the results of this study also highlight the importance of using the Deep Learning approach to improve the quality of understanding and high-level thinking skills among students.